PORTRAIT OF THE QUALITY OF MULTIPLE-CHOICE TESTS FOR ENGLISH LANGUAGE SUBJECTS ON STUDENTS - Wawan Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze test items on students' understanding in learning English. Test items used as an assessment must have objective quality that can be accounted for, so the questions are analyzed statistically which includes (1) validity analysis, (2) reliability analysis, (3) difficulty level analysis, and (4) question discrimination analysis. The form of research used in this study is quantitative descriptive research. This research is an evaluation involving 30 students. The instrument used in this study is data collection through documentation techniques. Analysis of the test item data was carried out using the SPSS 25 program. The results of the difficulty index test show that the test items are in the very easy category 20%, the test items are in the medium category 72% and the test items are in the easy category 20%. While the test results of the test show that the test items are at a very good level with a presentation of 4%, the questions are in the good category with a presentation of 64%, and the questions are in the sufficient category with a presentation of 24%. The questions presented can be analyzed with valid and reliable results and can be distributed well. Thus, it can be concluded that the questions are suitable for use in midterm exams. The benefits of this research include the need to always prepare backup questions to replace those deemed unsatisfactory, revisions to questions deemed good enough for reuse, and addition of questions deemed good to the question bank.